(untitled) (Indian Journal of Public Health Research & Development, 2024)
• BACKGROUND: Excessive alcohol consumption and consequent medical disorders are considerable problems in many countries. Aminotransferases (alanine aminotransferase ALT and aspartate aminotransferase AST) are the liver enzymes commonly used for detecting excessive drinking. Gamma-glutamyl transferase (GGT) is a membrane-bound glycoprotein enzyme widely used as an index of excessive ethanol intake. The aim of this study is to determine the changes in levels of ALT,AST and GGT in chronic alcoholic liver diseases. • MATERIALS AND METHODS: A cross-sectional study was done and included 100 individuals (50 chronic alcoholic liver diseases cases and 50 normal controls). Serum ALT, AST, GGT were estimated by colorimetric method on fully automated chemistry analyzer. • RESULT: Data were fed under Microsoft Excel 2007 and statistically analyzed by Graphpad software; Version 6.0, which evaluated the differences of various parameters in both groups on the basis of p value. Serum ALT, AST & GGT levels were significantly elevated in chronic alcoholic liver diseases patients as compared to normal healthy controls. • CONCLUSION: Chronic consumption of alcohol results in the secretion of pro-inflamatory cytokines(TNF alpha, Interleukin 6 [IL6] and Interleukin 8 [IL8]),oxidative stress, lipid peroxidation, and acetaldehyde toxicity. These factors cause inflammation, apoptosis and eventually fibrosis of liver parenchyma which leads to elevations in liver enzymes like AST & ALT. GGT is an enzyme produced in the bile duct. Measurement of GGT is an extremely sensitive test. It is induced by alcohol and its serum activity may be increased in heavy drinkers even in the absence of liver damage or inflammation. Hence these parameters should be regularly monitored in chronic alcoholic liver diseases